Assessment of Quality of Life and Speech after Implant-Retained Oral Rehabilitation in Head and Neck Cancer Patients. (17th June 2013) - Dholam, Kanchan P.; Pusalkar, Hrishikesh A.; Bachher, Gurmeet Kaur; Somani, Priyanka Piyush
Abstract : Aim . To assess quality of life and speech after rehabilitation with implant-retained dental prosthesis in head and neck cancer patients. Material and Methods . Twenty-six patients who were diagnosed with tumour of the maxilla and mandible were selected for rehabilitation with implant-retained dental prosthesis following resection and reconstructive surgery. They were evaluated for quality of life (EORTC QLQ-C30 and H-N35 questionnaires, version 3), speech, and swallowing (questionnaire and Dr. Speech software, version 4) before implant treatment and at six-, twelve-, and eighteen-month followup. Statistical analysis of quality of life, speech, and swallowing for different duration of their preoperative status was done. Quality of life, speech, and swallowing in grafted and native groups and radiated and nonradiated groups were also compared. Results . Quality of life was statistically significant in scale of pain, speech, and trouble with social eating, pain killers, and weight loss. It was insignificant when radiated and nonradiated or grafted and native jaw groups were compared. Improvement in movement of the tongue, swallowing ability, salivation taste, and intelligibility of speech was also observed. Conclusion . The surgical treatment of head and neck cancers with microvascular surgery and dental rehabilitation with implants restores function, esthetics, and patient's well-being.